PEMBERDAYAAN EKONOMI KERAKYATAAN MELALUI LEMBAGA KEUANGAN SYARÎ’AH - Wadhan - (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2009)
UKM is the business maker of the lowest level marketing. Theaim of the empowerment of UKM is that to grow and toaccelerate a strong business ability, independent, andcompetition power against abroad products. It is a proper choiceto use Syariah banking for UKM financing. Syariah banking has agreat opportunity to develop macro banking in order to reformIndonesian economy.